Rapid nanoparticle self-assembly at elevated temperatures. Issue 17 (18th April 2018) - Gerstner, Dominik; Kraus, Tobias
Abstract : We demonstrate that rapid nanoparticle self-assembly is possible in organic solvents if the temperature is above the melting point of the particles' ligand shell. Abstract : We demonstrate that rapid nanoparticle self-assembly is possible in organic solvents if the temperature is above the melting point of the particles' ligand shell. Flow experiments coupled to small-angle X-ray scattering reveal the agglomeration kinetics and agglomerate structures of alkylthiol-coated gold nanoparticles at different temperatures, interparticle potentials, and times. Our experiments allow to discriminate between the effects of long-range and short-range interactions on self-assembly: crystalline agglomerates formed for a wide range of potentials, but only at temperatures where the short-ranged mobility was sufficient. Rapid superlattice formation in less than 3 s was observed for strongly attractive potentials at high temperatures, implying an assembly rate that is sufficient for large-scale material synthesis. Strong attraction between the particles did not impede high-quality self-assembly when short-ranged mobility was provided by ligands above a specific temperature.